Orientasi Komitmen Ditinjau Dari Kepemimpinan Transformasional & Kepercayaan Terhadap Manajemen - , Sumaryono ([Yogyakarta] : Fak. Psikologi UII, 2005)
Abstract This research aimed at finding Human Resources Management pattem in Indonesian govennent owned business organization (BUMN). Focus of the research were finding comJ/ation pattern between commitment orientation and trust for management and transfonnational leadership. This research also assesed carrier-oriented commitment, team-oriented commitment, and organizational-oriented commitment. Data were collected from 208 employees at one BUMN in East Java. Three scales were used in this research: Orientation Commitment Scale, Trost for Management Scale, Transformational Leadership Scale. Data were analysed thing multiple regression. The results of the research are: a) Transfonnational Leadership and trust for management correlate with Commitment Orientation, b) Carrier-Oriented Commitment was influenced by trust for management, c) Transfonnational Leadership and tnJst for management correlate with Team-Oriented Commitment, d) Organizational-Oriented Commitment was influenced by Transfonnational Leadership.